Neuroprotection in Acute Ischemic Stroke: A Battle Against the Biology of Nature - Ghozy, Sherief; Reda, Abdullah; Varney, Joseph; Elhawary, Ahmed Sallam; Shah, Jaffer; Murry, Kimberly; Sobeeh, Mohamed Gomaa; Nayak, Sandeep S.; Azzam, Ahmed Y.; Brinjikji, Waleed; Kadirvel, Ramanathan; Kallmes, David F. (Frontiers in Neurology, 2022)
Stroke is the second most common cause of global death following coronary artery disease. Time is crucial in managing strokes to reduce the rapidly progressing insult of the ischemic penumbra and the serious neurologic deficits that might follow it. Strokes are mainly either hemorrhagic or ischemic, with ischemic being the most common of all types of strokes. Thrombolytic therapy with recombinant tissue plasminogen activator and endovascular thrombectomy are the main types of management of acute ischemic stroke (AIS). In addition, there is a vital need for neuroprotection in sitting of AIS. Neuroprotective agents are found to have profound benefits in improving mortality, lessening disability, and improving quality of life after AIS. In our review, we will discuss the main types of management and the different modalities of neuroprotection, their mechanisms of action, and evidence of their effectiveness in events of ischemia following stroke.